Sedative Activity of Argyreia populifolia Leaf Extract - Ratnasooriya, W. D.; Dharmasiri, M. G. (My University, 2001)
The sedative potential of a Sri Lankan endemic plant species, Argyreia populifolia Choisy (Family: Convolvulaceae) was tested using the leaf extract (2.5, 5.0 and lO.O ml/kg) on rats by placing them in the rat hole board apparatus. The extract had no sedative effect on male and oestrous rats. In contrast, in dioestrous rats, all the 3 doses of the extract tried and in pro-oestrous rats the highest dose induced marked sedation. The sedative effect had a slow onset and short duration of action. The sedative action of the extract was blunted in ovarectomised rats (rats whose both ovaries were removed) and in dioestrous rats treated with oestradiol. The extract had no toxic effects but phytochemical screening revealed the presence of flavonoids and alkaloids. !t was concluded that the sedation of A. populifolia leaf extract is mediated by its antihistamine activity via its alkaloids